2017
DOI: 10.1021/acsmacrolett.7b00927
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation Kinetics of Local Conformation of Polyisoprene at Substrate Interface

Abstract: The performance of a polymer composite material, in which inorganic fillers are dispersed, is closely related to the aggregation states and dynamics of polymer chains at the interface with the filler. In this study, the local conformation of polyisoprene (PI) at a quartz substrate interface was studied as a model system for the rubber/filler composite material. PI films were prepared from a toluene solution onto quartz substrates by a spin-coating method. Sum-frequency generation spectroscopy revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 65 publications
2
48
0
Order By: Relevance
“…If this speculation is true, the temporal face-on oriented structure should be relaxed to a randomly oriented structure, followed by crystallization by thermal annealing (or aging). 36 To confirm this expectation, the annealed film is investigated in the next section. When the low-wavenumber region is magnified (Figure 3c), the (C-H) bands specific to the monoclinic phase are found at 754 and 741 cm -1 (marked by "M") particularly in the IP spectrum implying some monoclinic 37 crystallites in the film, whose crystal structure is the same as that of a wet film prepared from a chloroform solution (Figure 1b).…”
Section: Resultsmentioning
confidence: 85%
“…If this speculation is true, the temporal face-on oriented structure should be relaxed to a randomly oriented structure, followed by crystallization by thermal annealing (or aging). 36 To confirm this expectation, the annealed film is investigated in the next section. When the low-wavenumber region is magnified (Figure 3c), the (C-H) bands specific to the monoclinic phase are found at 754 and 741 cm -1 (marked by "M") particularly in the IP spectrum implying some monoclinic 37 crystallites in the film, whose crystal structure is the same as that of a wet film prepared from a chloroform solution (Figure 1b).…”
Section: Resultsmentioning
confidence: 85%
“…Hence, it can be claimed that the relaxation of the SFG peaks is directly connected to the intrinsic dynamics of chains in the strongly adsorbed layer. 42 Similarly, we also reported that PI chains in direct contact with the SiO 2 surface were relaxed at (T g b + 125) K. 41 Although the adsorbed PI chains were fully relaxed with increasing temperature up to (T g b + 130) K, 41 such a full relaxation was not here observed for adsorbed NBR chains. At 423 K, (∼(T g b + 180) K), while the SFG peaks corresponding to different CH stretching vibration modes decreased, the peak arisen from CN groups increased, as shown in Figure 3.…”
mentioning
confidence: 73%
“…The dynamics of adsorbed chains on the solid surface are reported to be generally slower than the bulk dynamics. ,,, The extent of such a slowing down can be strongly dependent on the distance from the solid surface and temperature in addition to the characteristics of polymers and solid surface. ,, However, current understanding of the dynamics for adsorbed chains is generally obtained by simply modeling the interfacial polymer region as a single-layer, but the results still remain apparently controversial. ,,, , Several dielectric relaxation spectroscopy (DRS) results have indicated that adsorbed chains were not immobilized, but relaxed, even at a temperature near the T g b , and the segmental relaxation time was larger by a factor of 100 over a temperature range from ( T g b + 10) to ( T g b + 60) K. ,, In contrast, nuclear magnetic resonance (NMR) spectroscopy and thermal analysis have indicated the existence of an adsorbed layer just a few nanometers in thickness, in which the dynamics were frozen, even at a temperature far above the T g b , directly bound to the solid filler surface. , Our recent results on the basis of sum-frequency generation (SFG) spectroscopy also evidenced that adsorbed chains in direct contact with the SiO 2 surface were immobilized up to ∼80–120 K above the T g b , depending on the molecular nature of the polymer. Our SFG data further indicated that frozen adsorbed chains could be relaxed by annealing at a higher temperature. This is also supported by Kumar and co-workers in a recent report using a small angle neutron scattering technique .…”
mentioning
confidence: 99%
“…This scenario is indeed supported by our recent results on different polymers in contact with a substrate interface. 37,38 In contrast with the enhanced segmental motion of the polymer surface, the segmental motion of interfacial polymers at the substrate interface was observed to occur at temperatures more than 100 K above the bulk T g . 37,38 Although the peak intensity of the ν 2 mode gradually decreased with increasing temperature, it was still dominant at 400 K (Figure 1), 22 K above the bulk T g .…”
mentioning
confidence: 96%